Cancel Culture di Media Sosial: Dampaknya terhadap Kebebasan Berpendapat dan Resiliensi Psikologis Mahasiswa - Ike Dian Puspita Sari; Nurcholis Sunuyeko; Anita Kurnia Rachman (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study explores the phenomenon of cancel culture and its impact on freedom of speech and the psychological resilience of university students in Indonesia. Employing a qualitative approach with an existential phenomenological design, data were collected through in-depth interviews with 15 students who had been involved in the digital cancellation ecosystem as perpetrators, victims, or passive bystanders. The results reveal that cancel culture has mutated from an accountability instrument into a repressive form of digital vigilantism. Key findings indicate a massive chilling effect, where students obsessively practice self-censorship of their opinions due to the fear of destructive social exclusion. Furthermore, the study identifies severe psychological impacts on "cancelled" subjects, including panic attacks, depression, and social isolation that threatens academic motivation. The boundary between ethical enforcement and cyberbullying is found to be increasingly blurred due to the amplification of collective rage by social media algorithms. This study concludes that the dominance of this horizontal judgment culture has created a crisis of intellectual courage within the campus environment. Therefore, a paradigm shift toward restorative justice and the strengthening of digital emotional literacy is required to restore a safe dialectical space where differing opinions are no longer perceived as social threats that must be permanently eradicated.